An energy-saving color scheme for direct volume rendering. (February 2016) - Chen, Weifeng; Chen, Wei; Chen, Haidong; Zhang, Zhengfang; Qu, Huamin
Abstract: Energy-adaptive color selection or design has recently received much attention with the spreading of the organic light emitting diode (OLED) display. Current solutions optimize color sets by analyzing the energy consumption of the 2D rendered images with the screen-space energy model. The comprehensive influence with respect to the volume visualization like the illumination model, the light, as well as the semi-transparency is not considered. This paper presents an energy-saving color scheme selection and optimization approach for direct volume rendering on OLED displays. We propose an illumination-aware energy estimating model that formulates a simplified equation between the display energy consumption and a specific color scheme in object space, making it practical to achieve global color scheme optimization. By performing the color scheme optimization, we obtain an optimal color transfer function, with which we can generate energy-aware direct volume rendering images for OLED display. Experimental results demonstrate the efficiency of our approach on OLED display systems. Abstract : Graphical abstract: Abstract : Highlights: We propose a fast illumination-aware energy estimating model for 3D visualization. We formulate three perception-based quantified constraints. We propose a model based color design process for energy-saving display. It is the first effort to perform energy-saving 3D visualization on OLED display.